The Key Transcription Factor Expression in the Developing Vestibular and Auditory Sensory Organs: A Comprehensive Comparison of Spatial and Temporal Patterns - Shaofeng Liu; Yunfeng Wang; Yongtian Lu; Wen Li; Wenjing Liu; Jun Ma; Fuqin Sun; Mao Li; Zheng-Yi Chen; Kaiming Su; Wenyan Li (Neural Plasticity)
Inner ear formation requires that a series of cell fate decisions and morphogenetic events occur in a precise temporal and spatial pattern. Previous studies have shown that transcription factors, including Pax2, Sox2, and Prox1, play important roles during the inner ear development. However, the temporospatial expression patterns among these transcription factors are poorly understood. In the current study, we present a comprehensive description of the temporal and spatial expression profiles of Pax2, Sox2, and Prox1 during auditory and vestibular sensory organ development in mice. Using immunohistochemical analyses, we show that Sox2 and Pax2 are both expressed in the prosensory cells (the developing hair cells), but Sox2 is later restricted to only the supporting cells of the organ of Corti. In the vestibular sensory organ, however, the Pax2 expression is localized in hair cells at postnatal day 7, while Sox2 is still expressed in both the hair cells and supporting cells at that time. Prox1 was transiently expressed in the presumptive hair cells and developing supporting cells, and lower Prox1 expression was observed in the vestibular sensory organ compared to the organ of Corti. The different expression patterns of these transcription factors in the developing auditory and vestibular sensory organs suggest that they play different roles in the development of the sensory epithelia and might help to shape the respective sensory structures.